Systematic of foliicolous and phytopathogenic fungi associated with native plants of the Brazilian Cerrado stricto sensu - Abreu, Vanessa Pereira de (2019)
Cerrado is a home of huge diversity of endemic species of plants and animals. Therefore, it is considered a global biodiversity hotspot, however it is the Brazilian biome that has lost most native vegetation cover in recent years. Recent studies emphasize that the Cerrado may suffer the greatest extinction of plant species and consequently, the fungi suffer the same effects, because they are associated with vegetation and soil. They may also be threatened, and few studies have been carried out to discover the fungal diversity associated with Cerrado plant species. Knowledge of Cerrado micodiversity began with the activities of European collectors in the late 19th century and descriptions of new species and genera were based only on fungi morphology. Even the most recent descriptions were based only on morphological data without molecular information, which would allow the comparison and phylogenetic analyzes with other species in the world. The objective of this work was to determine and describe the foliicolous and phytopathogenic mycobiota associated with Cerrado native plants, based on morphological and molecular analyzes, as well as to establish the phylogenetic positioning of the species found and to initiate a fungal culture collection of this biome. A total of 82 plant materials were collected and 92 fungi belonging to several genera were isolated, when possible, and of these, six genera were selected for the taxonomy and molecular phylogeny studies. This study reports 3 possible new genera (Paraopeba, Dictyosporina and Trochilispora); 5 possible new species (Mastigosporella pigmentata, Pseudocercospora styracina, Trochilispora schefflerae, Dictyosporina ferruginea and Paraopeba schefflerae) and a possible epitypification (Uleomyces sanguineus) will be proposed. These results corroborate the great diversity of fungal species found by other researchers in the Cerrado biome and represent a contribution to the knowledge of the diversity of follicolous and phytopathogenic fungi associated with different native plants of the Floresta Nacional de Paraopeba (FLONA - Paraopeba).